Stakeholder capacity needs assessment and needs matrix validation: Case study of Mzimba, Kasungu, Balaka, Zomba, and Mangochi districts - Kachali, Righteous; Kaula, Norah; Chavula, Geoffrey; Chimonyo, Vimbayi G. P. (International Maize and Wheat Improvement Center, 2024)
Over the past ten years, Malawi has experienced significant changes in rainfall patterns, characterized by increased variability and unpredictability (Demissie and Gebrechorkos, 2024; USAID, 2013; WorldBank, 2022). Frequent extreme weather events, such as prolonged dry spells, late onset of rains, and sporadic heavy downpours, have become common (Amosi and Anyah, 2024; Demissie and Gebrechorkos, 2024; GoM, 2018; Nkhoma et al., 2021; USAID, 2024; World-Bank, 2019). These changes, coupled with soil degradation, including erosion and nutrient depletion, have exacerbated the challenges faced by farmers and the agricultural sector (Dinko and Bahati, 2023; Kaushik et al., 2023; McCarthy et al., 2021; Nutrients et al., 2018; Rezaei et al., 2023). Small landholding sizes, limited access to agricultural extension services, and restricted availability of quality inputs, such as improved seeds and fertilizers, and dysfunctional markets that do not adequately reward farmers, have further compounded these challenges (Adesina et al., 2014; Chibwana and Fisher, 2011; Gomez y Paloma et al., 2020; Lee et al., 2023; W. Munthali and Okori, 2018; Ragasa and Niu, 2017). Additionally, there is little integration and synergy between crop, animal, and agroforestry systems (Chirwa et al., 2003; Alves et al., 2017; Brown et al., 2018a).